Joint effects of predatory protists and predatory bacteria on driving the evolution of bacterial antibiotic resistance - Thi Bao-Anh Nguyen; Kenneth Dumack; Michael Bonkowski; Qing-Lin Chen; Tim Urich; Verena Groß; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Investigation of the seasonal dynamics of grassland soil bacterivores in top- and subsoils - Verena Groß; Mathilde Borg Dahl; Jana Täumer; Kenneth Dumack; Haitao Wang; Michael Bonkowski; Tim Urich (European Journal of Soil Biology, 2025)

Sea‐Ice Microbial Community Succession and the Potential Role of Parasitoids in the Maintenance of Diversity During the Spring Bloom - Kyle B. Dilliplaine; Laura M. Whitmore; Ana Aguilar‐Islas; Channing Bolt; Kenneth Dumack; Meibing Jin; Mette Kaufman; Marc Oggier; Gwenn M. M. Hennon (Environmental Microbiology, 2025)
Sea ice is a crucial, yet declining, habitat in high latitude ecosystems. Here we present a high‐temporal resolution amplicon sequence data set collected during the spring ice‐algal bloom near Utqiaġvik, Alaska in 2021 to study sea‐ice microbial dynamics. The ice‐algal bloom peaked on May 8th, reaching 46.6 mg chlorophyll a m −2 and thereafter became limited by nitrate availability. A massive bloom of the oil‐degrading bacterium, Oleispira (> 80% relative abundance), coincided with the algal bloom raising questions about hydrocarbon exposure. The sea‐ice algal bloom was dominated by diatoms, particularly, Nitzschia spp. and transitioned into a flagellate‐dominated postbloom community which aligned with melt‐associated changes to the physicochemical environment. We explored the relationship between putative parasitoids, Chytridiomycetes, Thecofilosea (Cercozoa), Oomycetes, Syndiniales (Dinoflagellata) and Labyrinthulomycetes (Bigyra) and potential microalgal hosts. Chytrids peaked periodically suggesting synchronised infections and Cryothecomonas (Thecofilosea) was observed parasitizing Nitzschia spp. for the first time in Arctic sea ice. Co‐occurrence analysis suggested that diatoms, especially Nitzschia , were the primary hosts of Pacific‐Arctic parasitoids and that top‐down parasitoid control may dramatically alter community composition over short timescales, such as days. These results provide important insights into the drivers of spring bloom timing and maintenance of microalgal diversity in sea ice.

Sludge retention time in anaerobic digestion affects Archaea by a cascade through microeukaryotes - Maria Badra; Jule Freudenthal; Kenneth Dumack (Water Research, 2025)

Profiling the eukaryotic soil microbiome with differential primers and an antifungal peptide nucleic acid probe (PNA): Implications for diversity assessment - Haotian Wang; Kenneth Dumack; Daniel V. Rissi; Damien R. Finn; Michael Bonkowski; Christoph C. Tebbe (Applied Soil Ecology, 2024)

The impact of fungi on soil protist communities in European cereal croplands - Florine Degrune; Kenneth Dumack; Masahiro Ryo; Gina Garland; Sana Romdhane; Aurélien Saghaï; Samiran Banerjee; Anna Edlinger; Chantal Herzog; David S. Pescador; Pablo García‐Palacios; Anna Maria Fiore‐Donno; et al. (Environmental Microbiology, 2024)
Protists, a crucial part of the soil food web, are increasingly acknowledged as significant influencers of nutrient cycling and plant performance in farmlands. While topographical and climatic factors are often considered to drive microbial communities on a continental scale, higher trophic levels like heterotrophic protists also rely on their food sources. In this context, bacterivores have received more attention than fungivores. Our study explored the connection between the community composition of protists (specifically Rhizaria and Cercozoa) and fungi across 156 cereal fields in Europe, spanning a latitudinal gradient of 3000 km. We employed a machine‐learning approach to measure the significance of fungal communities in comparison to bacterial communities, soil abiotic factors, and climate as determinants of the Cercozoa community composition. Our findings indicate that climatic variables and fungal communities are the primary drivers of cercozoan communities, accounting for 70% of their community composition. Structural equation modelling (SEM) unveiled indirect climatic effects on the cercozoan communities through a change in the composition of the fungal communities. Our data also imply that fungivory might be more prevalent among protists than generally believed. This study uncovers a hidden facet of the soil food web, suggesting that the benefits of microbial diversity could be more effectively integrated into sustainable agriculture practices.

It's time to consider the Arcellinida shell as a weapon - Kenneth Dumack; Enrique Lara; Clément Duckert; Elizaveta Ermolaeva; Ferry Siemensma; David Singer; Valentyna Krashevska; Mariusz Lamentowicz; Edward A.D. Mitchell (European Journal of Protistology, 2024)

Fungivorous protists in the rhizosphere of Arabidopsis thaliana – Diversity, functions, and publicly available cultures for experimental exploration - Antonie H. Estermann; Justin Teixeira Pereira Bassiaridis; Anne Loos; Marcel Dominik Solbach; Michael Bonkowski; Sebastian Hess; Kenneth Dumack (Soil Biology and Biochemistry, 2023)

Expansion of the cytochrome C oxidase subunit I database and description of four new lobose testate amoebae species (Amoebozoa; Arcellinida) - Giulia M. Ribeiro; Fernando Useros; Kenneth Dumack; Rubén González-Miguéns; Ferry Siemensma; Alfredo L. Porfírio-Sousa; Carmen Soler-Zamora; João Pedro Barbosa Alcino; Daniel J.G. Lahr; Enrique Lara (European Journal of Protistology, 2023)

Root traits explain multitrophic interactions of belowground microfauna on soil nitrogen mineralization and plant productivity - Junwei Hu; Ummehani Hassi; Mesfin Tsegaye Gebremikael; Kenneth Dumack; Tom De Swaef; Wim Wesemael; Steven Sleutel; Stefaan De Neve (Soil Biology and Biochemistry, 2023)

Microeukaryotic predators shape the wastewater microbiome - Nils Heck; Jule Freudenthal; Kenneth Dumack (Water Research, 2023)

Plant associated protists—Untapped promising candidates for agrifood tools - Bao‐Anh Thi Nguyen; Kenneth Dumack; Pankaj Trivedi; Zahra Islam; Hang‐Wei Hu (Environmental Microbiology, 2023)
The importance of host‐associated microorganisms and their biotic interactions for plant health and performance has been increasingly acknowledged. Protists, main predators and regulators of bacteria and fungi, are abundant and ubiquitous eukaryotes in terrestrial ecosystems. Protists are considered to benefit plant health and performance, but the community structure and functions of plant‐associated protists remain surprisingly underexplored. Harnessing plant‐associated protists and other microbes can potentially enhance plant health and productivity and sustain healthy food and agriculture systems. In this review, we summarize the knowledge of multifunctionality of protists and their interactions with other microbes in plant hosts, and propose a future framework to study plant‐associated protists and utilize protists as agrifood tools for benefiting agricultural production.

Hierarchical phylogenetic community assembly of soil protists in a temperate agricultural field - Julien Roy; Florent Mazel; Kenneth Dumack; Michael Bonkowski; Matthias C. Rillig (Environmental Microbiology, 2022)
Protists are abundant, diverse and perform essential functions in soils. Protistan community structure and its change across time or space are traditionally studied at the species level but the relative importance of the processes shaping these patterns depends on the taxon phylogenetic resolution. Using 18S rDNA amplicon data of the Cercozoa, a group of dominant soil protists, from an agricultural field in western Germany, we observed a turnover of relatively closely related taxa (from sequence variants to genus‐level clades) across soil depth; while across soil habitats (rhizosphere, bulk soil, drilosphere), we observed turnover of relatively distantly related taxa, confirming Paracercomonadidae as a rhizosphere‐associated clade. We extended our approach to show that closely related Cercozoa encounter divergent arbuscular mycorrhizal (AM) fungi across soil depth and that distantly related Cercozoa encounter closely related AM fungi across soil compartments. This study suggests that soil Cercozoa community assembly at the field scale is driven by niche‐based processes shaped by evolutionary legacy of adaptation to conditions primarily related to the soil compartment, followed by the soil layer, giving a deeper understanding on the selection pressures that shaped their evolution.

Contrasting protist communities (Cercozoa: Rhizaria) in pristine and earthworm-invaded North American deciduous forests - Kenneth Dumack; Olga Ferlian; Deisy Morselli Gysi; Florine Degrune; Robin-Tobias Jauss; Susanne Walden; Hüsna Öztoprak; Tesfaye Wubet; Michael Bonkowski; Nico Eisenhauer (Biological Invasions, 2022)
Earthworms are considered ecosystem engineers due to their fundamental impact on soil structure, soil processes and on other soil biota. An invasion of non-native earthworm species has altered soils of North America since European settlement, a process currently expanding into still earthworm-free forest ecosystems due to continuous spread and increasing soil temperatures owing to climate change. Although earthworms are known to modify soil microbial diversity and activity, it is as yet unclear how eukaryote consumers in soil microbial food webs will be affected. Here, we investigated how earthworm invasion affects the diversity of Cercozoa, one of the most dominant protist taxa in soils. Although the composition of the native cercozoan community clearly shifted in response to earthworm invasion, the communities of the different forests showed distinct responses. We identified 39 operational taxonomic units (OTUs) exclusively indicating earthworm invasion, hinting at an earthworm-associated community of Cercozoa. In particular, Woronina pythii , a hyper-parasite of plant-parasitic Oomycota in American forests, increased strongly in the presence of invasive earthworms, indicating an influence of invasive earthworms on oomycete communities and potentially on forest health, which requires further research.

Cascading effects from plants to soil microorganisms explain how plant species richness and simulated climate change affect soil multifunctionality - Enrique Valencia; Nicolas Gross; José L. Quero; Carlos P. Carmona; Victoria Ochoa; Beatriz Gozalo; Manuel Delgado‐Baquerizo; Kenneth Dumack; Kelly Hamonts; Brajesh K. Singh; Michael Bonkowski; Fernando T. Maestre (Global Change Biology, 2018)
Despite their importance, how plant communities and soil microorganisms interact to determine the capacity of ecosystems to provide multiple functions simultaneously (multifunctionality) under climate change is poorly known. We conducted a common garden experiment using grassland species to evaluate how plant functional structure and soil microbial (bacteria and protists) diversity and abundance regulate soil multifunctionality responses to joint changes in plant species richness (one, three and six species) and simulated climate change (3°C warming and 35% rainfall reduction). The effects of species richness and climate on soil multifunctionality were indirectly driven via changes in plant functional structure and their relationships with the abundance and diversity of soil bacteria and protists. More specifically, warming selected for the larger and most productive plant species, increasing the average size within communities and leading to reductions in functional plant diversity. These changes increased the total abundance of bacteria that, in turn, increased that of protists, ultimately promoting soil multifunctionality. Our work suggests that cascading effects between plant functional traits and the abundance of multitrophic soil organisms largely regulate the response of soil multifunctionality to simulated climate change, and ultimately provides novel experimental insights into the mechanisms underlying the effects of biodiversity and climate change on ecosystem functioning.

Organic matter composition and the protist and nematode communities around anecic earthworm burrows - Walter S. Andriuzzi; Phuong-Thi Ngo; Stefan Geisen; Aidan M. Keith; Kenneth Dumack; Thomas Bolger; Michael Bonkowski; Lijbert Brussaard; Jack H. Faber; Abad Chabbi; Cornelia Rumpel; Olaf Schmidt (Biology and Fertility of Soils, 2016)